Stellar flares detected with the Next Generation Transit Survey. Issue 3 (14th April 2021) - Jackman, James A G; Wheatley, Peter J; Acton, Jack S; Anderson, David R; Bayliss, Daniel; Briegal, Joshua T; Burleigh, Matthew R; Casewell, Sarah L; Gänsicke, Boris T; Gill, Samuel; Gillen, Edward; Goad, Michael R; et al.
ABSTRACT: We present the results of a search for stellar flares in the first data release from the Next Generation Transit Survey (NGTS). We have found 610 flares from 339 stars, with spectral types between F8 and M6, the majority of which belong to the Galactic thin disc. We have used the 13-s cadence NGTS light curves to measure flare properties such as the flare amplitude, duration, and bolometric energy. We have measured the average flare occurrence rates of K and early to mid-M stars and present a generalized method to measure these rates while accounting for changing detection sensitivities. We find that field age K and early M stars show similar flare behaviour, while fully convective M stars exhibit increased white-light flaring activity, which we attribute to their increased spin-down time. We have also studied the average flare rates of pre-main-sequence K and M stars, showing they exhibit increased flare activity relative to their main-sequence counterparts.